JMP®, JMP IN® , and JMP Serve ™ - C.H. Spiegelman (Chemometrics and Intelligent Laboratory Systems, 1991)
I explore the term "medical complications" (hereafter "complications") by investigating and differentiating the numerous types of events that tend to be described as complications. I distinguish medical errors from medical malpractice by suggesting that the latter involves negligence or breach of duty. I describe both types of events as being "reasonably foreseeable" (even if they tend to only be reasonably preventable in the latter case) in that they tend to occur due to malfunctions, breakdowns of protocols, etc., that can be anticipated. By contrast, force majeure events (e.g., earthquakes, acts of war, floods) are not reasonably foreseeable and not subject to the control of relevant parties. I distinguish between foreground risks and background: the former are those risks that are probabilistically or modally dependent on the particular intervention, whereas the latter are those risks, which are not significantly affected, probabilistically or modally, by the intervention in question. I then propose that complications should be thought of as all and only actualized foreground risks, which are distinct from medical errors and malpractice. I conclude by considering how my view opens the door to consider medical mistakes (often due to overworked clinicians) in a new light.